2014
DOI: 10.1007/s12639-014-0558-8
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiology and risk factors for Toxoplasma gondii among pregnant women in Arab and African countries

Abstract: The epidemiology of toxoplasmosis in pregnancy is a major issue for public health. Primary infection in pregnant women can lead to serious sequelae. This review examined current sero-epidemiology and risks factor data for Toxoplasma gondii in pregnant women in Arab and African countries. A systematic electronic search of published literature was conducted. Data were extracted from relevant studies. Seropositivity is high in both regions. African countries have higher seropositivity than Arab countries due to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 82 publications
5
31
2
Order By: Relevance
“…Contrary to this study, data presented by Shao et al [13] showed that gestational age was a significant risk factor. The highest seroprevalence of Toxoplasma antibodies (29.2%) was found in pregnant women at the first trimester is similar to the result of Alsammani [35] contrary to second and third semesters [4,24].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Contrary to this study, data presented by Shao et al [13] showed that gestational age was a significant risk factor. The highest seroprevalence of Toxoplasma antibodies (29.2%) was found in pregnant women at the first trimester is similar to the result of Alsammani [35] contrary to second and third semesters [4,24].…”
Section: Discussionsupporting
confidence: 73%
“…Other studies have reported that the risk of contracting T. gondii infection increases with age unlike the case in this study [34,35]. Though age was not a risk factor to the T. gondii infection, younger women <21 years were more infected compared to older women.…”
Section: Discussioncontrasting
confidence: 66%
“…Corroborating many other studies, the use of untreated water was found to increase the risk of infection with T. gondii (Mwambe et al, 2013;Alsammani, 2014) through the ingestion of oocysts in contaminated water. A higher prevalence of T. gondii infection has been found among pregnant women who drink water from the well than those who drink piped water (Ishaku et al, 2009).…”
Section: Discussionmentioning
confidence: 57%
“…A recent review of studies exploring seroepidemiology and T. gondii ’s potential risk factors in various Arab and African contexts reached similar conclusions regarding the seroprevalence of T. gondii being significantly associated with a woman’s age. 41 For instance, Mwambe et al 44 reported that a woman’s risk of T. gondii infection increases by 7% with each additional year of age. The possible reasons for this remain unclear and require further exploration, but previous authors have suggested that it may be due to more prolonged exposure to the identified risk factors, transmission routes, and the generally low public awareness of preventive methods.…”
Section: Discussionmentioning
confidence: 99%